How can a heterosexual man remove his body hair and retain his masculinity? Mapping stories of male body hair depilation. Issue 1 (2nd January 2019) - Clarke, Victoria; Braun, Virginia
ABSTRACT: This study explores the gendered body hair removal norm and the meanings of male body hair by examining young people's sense-making around male body hair removal. The novel technique of story completion was used to collect data from 102  psychology undergraduates. They were presented with a story "stem" featuring a young man (David) deciding to start body hair removal and asked to complete the stem. David was most often portrayed as a young heterosexual man who was excessively hairy, in the "wrong" places, was often subject to teasing and bullying, and was concerned about his diminished sexual capital. Hair removal did not always end "happily ever after" for David. While in some stories he "got the girl, " he was punished for his vanity and foolishness in others. These different endings arguably reflect currently ambivalent meanings around male body hair depilation. The production of a hairless, or less hairy, male body is both desirable and a potential threat to masculinity. The data spoke strongly to the power of social norms surrounding body hair practices and suggest that story completion provides a useful tool in interrogating the discourses that sustain these norms.